„Intravasal trocken – Gewebe voll“: interstitielles Ödem und Volumenmanagement in der Intensivmedizin - Schley, Gunnar; Willam, Carsten (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2021)
In the second phase of shock therapy, we regularly find fluid overload with edema in our patients, which not only involves the skin and interstitial tissue but can also impair kidney, liver and pulmonary function. Revision of the Starling principle and new insights into physiology of the endothelial glycocalyx have important implications for fluid therapy in intensive care medicine. Determination of fluid overload and an appropriate therapy with either diuretics or ultrafiltration are the focus of “late goal-directed fluid removal” management.
CRIS-Team Scopus Importer:2021-10-15
Keywords: Critical care; Endothelial cells; Fluid therapy; Sepsis; Shock